Full-color phosphors from amine-functionalized crosslinked hybrids lacking metal activator ions - Carlos, Luís D.; Sá Ferreira, Rute A.; De Zea Bermudez, Verónica; Ribeiro, Sidney José Lima [UNESP] (Wiley, 2001)
Sol-gel derived hybrids that contain OCH2CH2 (polyethylene glycol, PEG) repeat units grafted onto a siliceous backbone by urea, -NHC(=O)NH-, or urethane, -NHC(=O)O-, bridges have been prepared. It is demonstrated that the white light PL of these materials results from an unusual convolution of a longer lived emission that originates in the NH groups of the urea/urethane bridges with shorter lived electron-hole recombinations occurring in the nanometer-sized siliceous domains. The PL efficiencies reported here (maximum quantum yields at room temperature of ≈ 0.20 ± 0.02 at a 400 nm excitation wavelength) are in the same range as those for tetramethoxysilane-formic acid, and APTES-acetic acid, sol-gel derived phosphors. The high quantum yields combined with the possibility of tuning the emission to colors across the chromaticity diagram present a wide range of potential applications for these hybrid materials.
Keywords: Amines; Crosslinking; Electrons; Grafting (chemical); Molecular weight; Organic acids; Photoluminescence; Polyethylene glycols; Quantum theory; Sol-gels; Urea; Chromaticity; Electron-hole recombination; Formic acid; Quantum yield; Tetramethoxysilane; Urethane; Phosphors